Kalimat Imperatif dan Deklaratif dalam Teks Berita Politik di Tempo.co Edisi Agustus - September 2025 - Elita Asri Widyawati; Nadya Amelia Zulfi; Citra Anggraini Puspita Sari; Renny Fadhillah Aprilliany; Muhammad Isky Yanuar Najib; Asep Purwo Yudi Utomo; Mulyono Mulyono; Riri Kumalasari (Lembaga Pengembangan Kinerja Dosen, 2026)
News texts are a systematic way of conveying information that contains declarative and imperative sentences used to convey meaning directly and demonstrate the persuasive value of the news. The research goals are to analyze imperative sentences to understand how commands, requests, prohibitions, or invitations are conveyed so that they can influence the actions or responses of readers, as well as to analyze declarative sentences, which play an important role in constructing discourse structure and indicating the writer's position on the topic being discussed. This study was conducted using a qualitative descriptive method. This method was chosen because it can describe what is seen, heard, felt, and asked. The researcher considers qualitative descriptive research to accurately describe a situation without manipulating variables. This research concludes that imperative sentences elicit responses in the form of agreement and action, or rejection, either directly or indirectly. Meanwhile, declarative sentences serve as a guide or basis for understanding the context the speaker wishes to convey and can also be used to reinforce previously conveyed information to avoid ambiguity and misunderstanding when examining the meaning. This research is expected to be useful in linguistic studies, more specifically in syntactic material that discusses declarative and imperative sentences in news texts and political discourses.